(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: Polycystic Ovarian Syndrome (PCOS) significantly impacts the quality of life (QoL) among women of reproductive age. In college students, the psychological and physical effects of PCOS can interfere with academic performance and well-being. Nurse-led interventions using lifestyle modifications are promising strategies to manage PCOS symptoms holistically. Methods: A systematic review and narrative analysis was conducted according to PRISMA guidelines. Four electronic databases (PubMed, CINAHL, Scopus, and Web of Science) were searched for English-language peer-reviewed studies published between 2011 and 2023. Boolean operators were used to identify relevant articles on nurse-led interventions incorporating yoga, dietary modifications, and exercise in college-aged women with PCOS, Twenty-five studies meeting the inclusion criteria were selected. Thematic analysis was performed using Braun and Clarke’s six-step framework. Results: Nurse-led interventions were consistently associated with improvements in emotional well-being, symptom management, menstrual regulation, body image, and metabolic outcomes. Yoga demonstrated benefits in reducing stress and cortisol levels; dietary guidance improved weight and insulin sensitivity; and exercise enhanced physical stamina and mood. Nurse facilitation contributed to better adherence, patient education, and ongoing support. Conclusion: The findings suggest that nurse-led lifestyle interventions incorporating yoga, diet, and exercise are effective in improving the QoL of college students with PCOS. These interventions should be incorporated into college health services to provide holistic, accessible, and evidence-based care.